Pengembangan Bentuk Latihan Tendangan Kuda B Berbasis Kearifan Lokal pada Atlet Pencak Silat - G Bula, Yuyun; Haryani, Meri; Kadir, Suprianto; Nurkhoiroh; Irawan, Safri (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
This research aims to produce a media for the Form of Horse Kick B (Double) Horse Kick Exercises Based on Local Wisdom in Single Art Pencak Silat Athletes. This research is a Research and Development (R&D) using the Plomp design model, the Plomp development model consists of three stages, namely the Initial Investigation Stage, the Prototype Making Stage, and the Assessment Stage. The subjects in this study were divided into two groups, namely the Experimental Group of 15 Pohuwato Sacred Tapak Athletes and the Control Group of 5 Pohuwato Sacred Tapak Athletes. The media of this book is assessed by material experts, linguists, and media experts using questionnaires. The data collection technique in this study is to make observations, distribute questionnaires filled out by athletes as research subjects and test tests and research documentation. The data results are in the form of qualitative data that are analyzed using qualitative descriptive and descriptive statistical analysis. The results of the research were obtained from the product media of the book of Horse Kick Exercise B (Double) with the title of the book Forms of T2lohand Exercises Based on Gorontalo local wisdom. The results of the overall feasibility percentage obtained from material experts, linguists, media experts, and respondent responses (FGD) show that the product of the T2Lohand Exercise book is free of the local wisdom of Gorontalo